PENGEMBANGAN KURIKULUM MADRASAH DINIYAH TAKMILIYAH - Salahuddin, Marwan (IAIN Ponorogo, 2012)
Abstract: The existence of Madrasah Diniyah Takmiliyah has significantly contributed to the development of educational field in Indonesia, especially in Islamic education. In relation to this, the system of school management needs to be reorganized, especially in term of curriculum, in which it should always be adapted to the development of science and technology, particularly in education. By restructuring the curriculum, it is expected that this Madrasah will be needed by the society all of the time, which in turn will impact on the extent of development over the symbols of Islam. There are some important aspects of curriculum that need to be laid back, as follows: the purpose, content, organization and strategy and its development orientation that adapts to the rapid change of education nowadays. Meanwhile, the development should be begun with the development at the institutional level in advance, such as by improving the vision, mission, competency standards of graduation, determination of the content and structure of the program and the development of learning methods/strategies. Furthermore, the syllabus development of each subject should be fitted in the graduation competency standards, standards of competence and basic competence. Finally, the development in the classroom during the learning process should be suited with the studentsâ characteristics and environmental conditions, teacher capability and the availability of school facilities.